Reforming medical career progression: a call for merit-based systems - Bulletti, Francesco Maria; Guido, Maurizio; Coccia, Maria Elisabetta; Palagiano, Antonio; Giacomucci, Evaldo; Bulletti, Carlo (Frontiers in Medicine, 2025)
ObjectiveTo identify and address systemic barriers undermining the meritocratic advancement of medical professionals in Italy and to propose a transparent, performance-driven recruitment model.Study designA critical narrative review and conceptual framework proposal supported by an analysis of current systemic limitations and international benchmarking data.MethodsWe conducted a narrative review involving structured searches of international and Italian sources, followed by thematic synthesis and the development of two merit frameworks—Merit-based Professional Value Score (MPVS) and Integrity and Impact Score (IIS)—featuring standardized indicators and peer-normalized scoring metrics.ResultsItaly's medical system, despite high economic capacity, underperforms due to persistent non-meritocratic structures. Key challenges include political interference in residency selection, low return rates of expatriated physicians (>11,000 currently practicing abroad), and biased hiring mechanisms. Women and internationally trained candidates encounter disproportionate barriers. Across medical systems, output-only metrics (e.g., H-index) has proven insufficient. We propose MPVS and IIS as transparent, auditable tools that integrate risk-adjusted outcomes, patient safety indicators, patient-reported measures, teaching, research, and integrity domains. A worked example illustrates end-to-end scoring process and decision thresholds. Furthermore, a new protocol is proposed featuring anonymized candidate evaluation based on two metrics:Medical Professional Value Score (MPVS)—integrates clinical outcomes, teaching performance, and professional conduct.Impact Innovation Score (IIS)—evaluates research relevance, innovation capacity, and applied contributions. Cross-linked digital verification, external audits, and rotating blinded selection panels under national anti-corruption oversight form the governance backbone.ConclusionImplementing this model would help reverse Italy's brain drain, restore merit-based standards in healthcare sector, and provide a replicable framework for other health systems pursuing transparency, quality, and equity.